Purification of Proplatelet Formation (PPF) Stimulating Factor: Thrombin/Antithrombin III Complex Stimulates PPF of Megakaryocytes In Vitro and Platelet Production In Vivo - Ishida, Yoji; Yano, Kazuo; Ito, Toshiharu; Shigematus, Hiroki; Sasaki, Kohsuke; Kondo, Shuhei; Kuriya, Shin-Ichiro (Thrombosis and Haemostasis, 2001)
In this study, the protein which stimulates proplatelet formation (PPF) of megakaryocytes was purified from normal human plasma using 7 steps procedures. Two different protease inhibitors were identified based on their amino acid sequences, i.e. antithrombin III (AT III) and C1 inhibitor. They were included in high density lipoprotein (HDL). HDL was necessary for AT III to be active in PPF in vitro. The biological effects of the AT III /HDL or thrombin-AT III (TAT)/HDL were studied in vitro. PPF of murine megakaryocytes was stimulated by negative control (BSA) (1.8 ± 0.3%), AT III (2.0 ± 0.4%), HDL (1.2 ± 0.9%), AT III /HDL (14.8 ± 2.1%) or TAT/HDL (23.3 ± 3.5%), respectively. TAT/HDL also had a synergistic effect with the mpl ligand, judging by the acetylcholinesterase (AchE) expression of murine megakaryocytes (2.7 fold increase). In vivo subcutaneous administration of AT III alone or TAT for 3 days significantly stimulated thrombocytosis (136% and 144%, respectively, p <0.05) and AT III/HDL showed rapid and further stimulation (150%, p <0.01). These results and the previous studies indicate that megakaryocytopoiesis is regulated by the mpl ligand, while a protease/protease inhibitor complex such as TAT, which is involved in the coagulation cascade associated with platelet consumption, might be one of the regulators in platelet production.
Keywords: Thrombocytopoiesis; proplatelet formation stimulating factor; anti-thrombin III; thrombin; high density lipoprotein